Enabling the new economic actor: personal data regulation and the digital economy - Crabtree, Andy (2016)
This paper offers a sociological perspective on data protection regulation and its relevance to the design of digital technologies that exploit or ‘trade in’ personal data. From this perspective, proposed data protection regulations in Europe and the US seek to create a new economic actor – the consumer as personal data trader – through new legal frameworks that shift the locus of agency and control in data processing towards the individual. The sociological perspective on proposed data regulation recognises the reflexive relationship between law and the social order, and the commensurate need to balance the demand for compliance with the design of tools and resources that enable this new economic actor; tools that provide both data protection to the individual and allow the individual to exploit personal data to become an active player in the emerging data economy.